The time dependent investigation of methane-air counterflow diffusion flames with detailed kinetic and pollutant effects into a micro/macro open channel - Ali Edalati-nejad; Sayyed Aboozar Fanaee; Maryam Ghodrat; Fatemeh Salehi; Javad Khadem (Case Studies in Thermal Engineering, 2020)
In the present study, time-dependent numerical analysis of methane-air counterflow diffusion flame into a selected macro/micro open channel is investigated. The flame is simulated by multi and single-step reaction approaches into an open channel with a constant distance of 15 mm between air and the fuel inlet, and a hydraulic distance at the order of 0.1 mm. To solve the unsteady problem, a coupled pressure-velocity implicit division method is considered. The results show an acceptable agreement between numerical and experimental data that confirm the accuracy of the model. The results also revealed that the variation of the residence time to the inlet velocity is more sensitive than the inlet temperature. It is also found that at the larger inlet velocities, the flame is stabilized at a smaller value of hydraulic distance. This is a result of increasing the possibility of reactions between species. The generation rates of CO2, CO and H2O species are found to be nearly constant at t > 0.009s while for NO and NO2 species the rates remain unchanged at t > 0.013s and t > 0.016s, respectively. Keywords: Counterflow diffusion flame, Detailed mechanisms, Time-dependent model, Micro/macro open channel